1992
DOI: 10.1111/j.2044-8309.1992.tb00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Judgements about victims and attackers in depicted rapes: A review

Abstract: This paper reviews the effects on subjects' judgements of a variety of factors that have been included in experimental depictions of rape. The focus is on attribution of responsibility or fault to the victim or attacker and related judgements, particularly regarding guilt and sanctions. Generally, females make more pro-victim judgements than do males, and people with non-traditional sex-role attitudes make more pro-victim judgements than do holders of more traditional views. Other factors covered are various v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
202
4
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(234 citation statements)
references
References 65 publications
22
202
4
1
Order By: Relevance
“…Research has found many factors that contribute to these judgements. One of the most frequently replicated findings is that men exhibit more punitive attitudes toward female rape victims than women (Pollard, 1992;Jiminez & Abreu, 2003;Joohee, Pomeory, Seo-Koo, Y. & Rheinboldt, 2005;Nagel, Matsuo, McIntyre & Morrison, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found many factors that contribute to these judgements. One of the most frequently replicated findings is that men exhibit more punitive attitudes toward female rape victims than women (Pollard, 1992;Jiminez & Abreu, 2003;Joohee, Pomeory, Seo-Koo, Y. & Rheinboldt, 2005;Nagel, Matsuo, McIntyre & Morrison, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…More research is needed on correlates of the actual reactions of support providers to real rape victims. It was hypothesized that younger, unmarried, ethnic minority victims with less education and income would report more negative social reactions from others upon disclosing their assaults (Ullman, 1999;Pollard, 1992;Ward, 1995), but the same number of positive social reactions from others. These hypotheses were based on the premise that women belonging to vulnerable social statuses would be more likely to be treated poorly after sexual assault, because of society's stereotypes that these women are more deserving of their victimization (Campbell, 1998).…”
mentioning
confidence: 99%
“…The secondary victimization of being blamed by others may have many negative consequences for a victim (e.g. Campbell & Raja, 1999Campbell, Sefl, Barnes, Ahrens, Wasco, Zaracgoza-Diesfeld, 1999;Pollard, 1992). The generally low report level of rape suggests that victims indeed seem to avoid secondary victimization, which indicates that blaming reactions constitute a serious societal problem (e.g.…”
Section: Introductionmentioning
confidence: 99%